STRATEGI PENGEMBANGAN PERBANKAN SYARIAH DI INDONESIA - Masulah, Siti (Jurnal Akuntansi AKUNESA, 2014)
Community is difficult to break away from the tradition of saving money in conventional banks which had stood earlier than Islamic banks. This study is to provide understanding to the public about Islamic banking. The purpose of this study to introduce Islamic banking as a financial institution that has a product that is different from conventional banks. Islamic banks are expected to become a new alternative for customers who will be the choice of investmentKeywords: Islamic banking, introduce Islamic banking , product